Decision Points in Application of Genetic Algorithm - Mahapatra, Biplab; Mohapatra, Sanjay (2015 International Conference on Information Technology (ICIT), 2015)
Selecting runtime parameters while applying Genetic Algorithm is a crucial decision. Numerous theoretical and empirical researches are performed and guidelines are suggested on this, researches are conducted but still an overall acceptable guideline is lacking. In this work the parameters are discussed with reference to the existing literature and suggested a guideline to follow for initial setup based on literature.